2015
DOI: 10.1126/sciadv.1500715
|View full text |Cite
|
Sign up to set email alerts
|

Frost for the trees: Did climate increase erosion in unglaciated landscapes during the late Pleistocene?

Abstract: Frost processes more than doubled erosion rates in unglaciated terrain during the Last Glacial Maximum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 74 publications
6
102
0
Order By: Relevance
“…Changes in temperature can affect physical weathering due to temperature-induced changes in periglacial processes and promote frost cracking, frost creep (e.g. Matsuoka, 2001;Schaller et al, 2002;Matsuoka and Murton, 2008;Delunel et al, 2010;Andersen et al, 2015;Marshall et al, 2015), and biotic weathering and erosion (e.g. Moulton and Berner, 1998;Banfield et al, 1999;Dietrich and Perron, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in temperature can affect physical weathering due to temperature-induced changes in periglacial processes and promote frost cracking, frost creep (e.g. Matsuoka, 2001;Schaller et al, 2002;Matsuoka and Murton, 2008;Delunel et al, 2010;Andersen et al, 2015;Marshall et al, 2015), and biotic weathering and erosion (e.g. Moulton and Berner, 1998;Banfield et al, 1999;Dietrich and Perron, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…10, 11), which may favour frost-driven weathering during glacial climate states (e.g. Andersen et al, 2015;Marshall et al, 2015) in unglaciated areas, whereas glacial processes would have dominated most of this region as it was covered by ice. Simulation PLIO is distinguished by temperatures that exceed PI and MH conditions by ca.…”
Section: St Elias Mountains Southern Alaskamentioning
confidence: 99%
See 1 more Smart Citation
“…In this special issue of ESPL, the great depths of weathering and modest erosion rates reported in two studies imply long legacies of past environments on weathering profiles developed in the Sierra Nevada, California (Holbrook et al , ), and in the mountains of Puerto Rico (Buss et al , ). In a recent study of the influence of Pleistocene climate on paleo‐erosion rates in the Oregon Coast Ranges, Marshall et al () have suggested that peri‐glacial processes during past climates may have widespread implications for interpreting observations of the CZ.…”
Section: Observations Of the Deep Czmentioning
confidence: 99%
“…Periglacial processes have also been suggested to be a key controlling factor for erosion (e.g. Marshall et al, 2015;Dosseto and Schaller, 2016): erosion is enhanced during cold periods in regions where they occur, whereas it is enhanced during warmer periods in regions exempt of periglacial processes. Mass wasting processes could be the main driver for erosion increase during wet periods (e.g.…”
Section: Impact Of Climate Changementioning
confidence: 99%